Circulating miRNAs act as potential biomarkers for asthma - Hu, Guang; Du, Yujie; Xie, Manying; Chen, Rongchang; Shi, Fei (Frontiers in Immunology, 2023)
Identification of new clinical markers contributes to a better understanding of the pathogenesis of asthma. Considering the crucial role of LIGHT in asthma, it may become a potential target for asthma. The aim of current study was to determine if circulating microRNAs (miRNAs) targeting LIGHT may be used as diagnostic biomarkers to distinguish asthma.Methods: Blood serum from a cohort of 60 subjects, including 20 cases with mild asthma, 20 cases with moderate-tosevere asthma, and 20 healthy controls were included. Serum was analyzed for circulating miRNAs profiles through miRNAs microarray. Real Time PCR was conducted to verify the results of miRNA microarray. Correlations be tween circulating miRNAs targeting LIGHT and clinical characteristics were investigated.Results: A total of 365 miRNAs were differentially expressed in asthma patients. Among them, miR-107 and miR-140-5p were found to target LIGHT, and varied in asthmatics. Additionally, miR-107 and miR-140-5p expressions were positively correlated with the absolute value of peripheral eosinophils. Finally, miR-140-5p and miR-107 were demonstrated to have good diagnostic efficacy for asthma (AUC= 0.8667 and 0.9400) with good sensitivity (0.8000 and 0.8667 separately,respectively) and specificity (0.8667 and 0.867). Thus, circulating miRNAs ex -pressed differentially between healthy control and asthma patients. Conclusions: Plasma miR-140-5p and miR-107 can be used as diagnostic biomarkers to distinguish patients with asthma from healthy control, and may take part in asthma pathogenesis by negatively regulating LIGHT. Further research was needed to evaluate their roles as poten tial biomarkers in the diagnosis of asthma.